Composite of La0.9Sr0.1Ga0.8Mg0.2O2.9Fe0.1 and ZrO2 as Solid Electrolyte in Solid Oxide Fuel Cell (SOFC) - RONA M.S. (NIM 10504060), TIRTA
Ideal characteristics of solid electrolyte for SOFC are high ionic conductivity, low electric conductivity, endure with shock thermal, and low price production. Solid electrolytes with high conductivity which have been widely used are lanthanum galate doped by stronsium and magnesium (LSGM) and stabilized zirconia. Electrolyte from stabilized zirconia cannot be used at low temperature while LSGM has a very high ionic conductivity at low temperature but did not have the toughness of stabilized zirconia. In this research, electrolyte composite with variety of composition of ZrO¬2 and LSGM doped Fe (LSGMF) were made with temperature of sintering at 1350oC for 12 hours, with composition of ZrO2 : LSGMF 90:10, 80:20, 75:25, 65:35, and 60:40 (%w/w). The ionic conductivity was measure by DC measurements with two probes method and AC measurements. XRD analysis showed that there is no reaction between LSGMF and ZrO2. SEM EDX and AC measurements revealed that the highest ionic conductivity with low activation energy was given by composite with composition of 75:25.